Multikultural Education’s Concept and It’s Value In The Qur’an - Amul Husni Fadlan; L Lutfiyani; Nur Edi Prabha Susila Yahya (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2018)
Basically, Multikultural’s education is not contradict with theteaching of Islam especially Qur’an which becomes the source of law inIslam. The diversity is actually becomes the rich of intelectual’s wealthfor reviewed. As it is in some verses of Qur’an which explains aboutthat. Hoefully with the existence of multikultural’s education, everyindividual or group should be expected to receive and appreciate manydifferences, they live together with peace and prosperous. This writingwill discuss about the multikultural’s education concept and theeducation’s value in the Qur’an. Therefore, the writer try to find theinformation to replied that problems, through the study exegis ofinterpretation the verses in Qur’an which is relevant the problems. Thisstudy has some goals, aimed to anaylyze: 1. The multikultural’seducation concept based on the thought of some education’s expert, 2.To know the multikultural’s education vales which can be found inQur’an, 3. Multikultural’s education urgency in contemporary Islamiceducation, nowadays. From the end of study, it can be conclude that:multikultural’s education is not contradict with the teaching of Islam.More over the multikultural’s education are also found in Qur’an. Forexample are learning to live in the diversity, buliding the mutual trustand mutual understanding, mutual respect, openminded in thinking,appreciation and interdependency, confilct’s resolution andreconciliation.